2016
DOI: 10.5021/ad.2016.28.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Role of Arachidonic Acid in Promoting Hair Growth

Abstract: BackgroundArachidonic acid (AA) is an omega-6 polyunsaturated fatty acid present in all mammalian cell membranes, and involved in the regulation of many cellular processes, including cell survival, angiogenesis, and mitogenesis. The dermal papilla, composed of specialized fibroblasts located in the bulb of the hair follicle, contributes to the control of hair growth and the hair cycle.ObjectiveThis study investigated the effect of AA on hair growth by using in vivo and in vitro models.MethodsThe effect of AA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Several reports demonstrated that hair growth agents promoted the proliferation and survival of DPC through the activation of ERK1/2 and Akt [3234]. The ERK signaling is known to be activated by mitogens in all types of mammalian cells and its key roles in cell growth have been established previously [35].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports demonstrated that hair growth agents promoted the proliferation and survival of DPC through the activation of ERK1/2 and Akt [3234]. The ERK signaling is known to be activated by mitogens in all types of mammalian cells and its key roles in cell growth have been established previously [35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, various other compounds have demonstrated stimulatory effect on DPCs at molecular level .…”
Section: Hair Growth Promoting Effectmentioning
confidence: 99%
“…The hair follicle (HF) is composed of epidermal (epithelial) and dermal (mesenchymal) compartments and their interaction has an important role in the morphogenesis of hair, growth of the hair follicle, and the hair cycle [23]. The dermal papilla, composed of specialized fibroblasts located in the bulb of the hair follicle, contributes to the control of hair growth and the hair cycle [21].…”
Section: Discussionmentioning
confidence: 99%
“…Isolated human scalp hair follicles were cultured as described previously [20,21]. Each HF was cut at the level of the sebaceous duct, and then cultured for 12 days at 37°C (5% CO 2 ) in Williams' E medium (Gibco-BRL laboratories, Grand Island, NY, USA), supplemented with 10 ng/ml hydrocortisone, 10 μg/ml insulin, 2 mM L-glutamine, and antibiotic/antimycotic 1x solution (penicillin and streptomycin, Gibco-BRL laboratories).…”
Section: Human Hair Follicles Organ Culture and Immunofluorescence Stmentioning
confidence: 99%